Genotyping of Bangladeshi Onion (Allium cepa L.) Germplasm for Male Sterility Using PCR-Based Molecular Markers (Journal of the Bangladesh Agricultural University, 2025)
Increasing onion productivity requires the development of hybrid varieties. Identification of sterile and maintainer lines is essential for successful hybrid development. This study aimed to identify cytoplasmic types: fertile (N) or sterile (S) and genotypic conditions at the Ms locus within the Bangladeshi onion germplasm, including certain mutant lines. The cytoplasmic marker accD was employed to differentiate between sterile and fertile cytoplasm, while three nuclear molecular markers (OPT, PsaO, and jnurf13) were used for genotyping the Ms alleles. The findings of the accD marker indicated that the frequency of fertile (N) cytoplasm was significantly higher than that of the sterile (S) cytoplasm. The result of nuclear markers also showed that the molecular markers used in this experiment are not sufficiently effective for accurate genotyping of the Ms locus due to the lack of linkage disequilibrium, suggesting the need to assess more closely linked markers for improved results, or the compromised genotypic purity of the collected germplasm may also be the reason of inconclusive genotyping. Nonetheless, molecular markers have proven highly effective for distinguishing between S and N cytoplasm. Utilizing these markers for cytotype (N/S) identification in onions will be helpful for the development of hybrid onions in the future.J Bangladesh Agril Univ 23(1): 1–8, 2025